Mapping the woman's body in Michael Ondaatje's The English patient - Burcar, Lilijana (ELOPE (Ljubljana), 2004)
Th is article shows that fixed national identities in Ondaatje's The English Patient are not only questioned but relinquished in favour of a flux of multiple, incessant becomings, while the specificity of a woman's identity, far from being decentred and evacuated of its discursively produced socio-symbolic meanings, continues to be addressed in terms of supposedly homogeneous female body and its institutionally sanctified appearances. Imbued with socially marked distinctiveness, such female body consequently gives forth a particular embodiment of feminine which comes to operate as its unproblematic facticity, thus simultaneously narrowing down the scope of identity options from which the feminine is compelled to derive the makeup of its very much truncated existence. The paper then seeks to apply the argumentdeveloped here to a classroom situation and students' creative approach towards redressing the problem of gendering the text at the expense of women characters by lending them their own voice.
Keywords: kanadska književnost; literarne študije; Ondaatje, Michael; Ondaatje, Michael: Angleški pacient; Ondaatje, Michael: The English patient; psihologija spolov; ženske